Estimation of indoor 222Rn concentration in Lima, Peru using LR-115 nuclear track detectors exposed in different modes - Liza Neciosup, Rafael Ángel (2023)
Radon is the main source of natural radioactivity, and its measurement is considered extremely important in radioprotection, given its relationship with the occurrence of lung cancer. In the last two years, measurements of this radioactive gas were carried out in Lima considering a grid of 5 km2 and the population density to determine the number of measurements to be carried out. Cellulose nitrate nuclear track detectors exposed in bare mode and diffusion chamber mode were used to estimate 222Rn concentrations. In diffusion chamber mode, non-commercial monitors and commercial monitors were used. The monitoring results are presented for 43 districts of the Lima Province whose population is approximately ten million inhabitants occupying a total area of 2655.15 km2. Measurements were made obtaining an average concentration of 49 Bq·m−3 using bare detectors and 66 Bq·m−3 using non-commercial diffusion chambers. Average concentrations obtained by both detector exposure modes were below the maximum concentration recommended by the WHO. A radon (222Rn) map was also obtained as a visual representation of the 222Rn levels in the Lima province using inverse distance weighting (IDW) interpolation.